2014
DOI: 10.1097/ico.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pseudodendrites in Herpes Zoster Ophthalmicus With Topical Ganciclovir 0.15% Gel

Abstract: Topical 0.15% ganciclovir gel, 5 times a day until pseudodendritic lesion healing and tapering to bid for 2 to 4 weeks thereafter, is an effective treatment for pseudodendrites in HZO-affected cases that are often a challenge to manage with other oral or topical antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…16 In 4 patients who developed corneal epithelial dendriform keratitis despite administration of oral valacyclovir, treatment with ganciclovir 0.15% gel resulted in healing.…”
Section: Discussionmentioning
confidence: 98%
“…16 In 4 patients who developed corneal epithelial dendriform keratitis despite administration of oral valacyclovir, treatment with ganciclovir 0.15% gel resulted in healing.…”
Section: Discussionmentioning
confidence: 98%
“…In 1995, a study showed that late epithelial dendriform keratitis lesions were often PCR-positive for VZV, and this was confirmed in 2010 by a larger series 61 62. Dendriform keratitis’ response to antiviral treatment is further evidence that it is caused by active VZV infection 58 62. VZV DNA has been found to persist in the saliva of 67% (21/32) of people with a past history of HZ up to 12 years after disease onset,70 but not in the saliva of healthy people 71…”
Section: Rationale For Investigation Of Suppressive Antiviral Treatmementioning
confidence: 95%
“…Long-term topical corticosteroids are needed to control stromal keratitis, endothelialitis and/or uveitis in most patients with chronic HZO disease (figures 2, 3A, B, 4 and 5). Effective treatment for dendriform keratitis is topical gangciclovir five times a day for 2 weeks and then twice daily for 2–4 weeks 58. Use of long-term suppressive oral antivirals is highly variable 59…”
Section: Rationale For Investigation Of Suppressive Antiviral Treatmementioning
confidence: 99%
“…16 Dendriform lesions respond to topical and systemic antiviral treatment. 6,7 In addition, corneas removed from HZO patients during transplantation have been found by PCR to have specific VZV genomic DNA sequences up to 51 years after HZO onset. 8 Furthermore, the Acyclovir Prevention Trial of the Herpetic Eye Disease Study (HEDS) determined that prolonged suppressive antiviral treatment significantly reduced recurrent eye disease caused by Herpes Simplex Virus (HSV), a different herpes virus, and was most beneficial in stromal keratitis, a disease manifestation considered to be immune mediated with the role of active viral infection unknown.…”
Section: Introductionmentioning
confidence: 99%